Bioethical knowledge in students and health professionals: a systematic review - González-Blázquez, Francisco Javier; Ruiz-Hontangas, Antonio; López-Mora, Clara (Frontiers in Medicine, 2024)
Bioethics training is essential for healthcare professionals as it enables them to address ethical dilemmas in their clinical practice. However, there is still a lack of rigorous teaching programs, and assessing bioethical knowledge poses challenges.Methodology: Systematic review using the PRISMA method.: Analysis of 27 studies reveals a lack of ethical knowledge and skills among healthcare professionals and students. Specific training in bioethics is effective in developing bioethical competencies. Different approaches have been employed, including integrated training in academic curricula and intensive or ongoing programs. The results demonstrate improvements in knowledge, attitudes, and ethical values, although regularly updating these courses is recommended.Conclusions: Specific training, institutional support, and considering regional and disciplinary differences are necessary to enhance ethics in the practice of healthcare professionals.